Differentiation between early rheumatoid arthritis patients and healthy persons by conventional and dynamic contrast-enhanced magnetic resonance imaging. (March 2014) - Axelsen, MB; Ejbjerg, BJ; Hetland, ML; Skjødt, H; Majgaard, O; Lauridsen, UB; Hørslev-Petersen, K; Boesen, M; Kubassova, O; Bliddal, H; Østergaard, M
<x xml:space="preserve">Abstract</x> Objectives: To identify the magnetic resonance imaging (MRI) parameter that best differentiates healthy persons and patients with early rheumatoid arthritis (RA), and to investigated responsiveness to treatment of various MRI parameters. Method: Conventional MRI and dynamic contrast-enhanced (DCE)-MRI of the hand were performed once for 26 healthy persons, and before and after 6 and 12 months of disease-modifying anti-rheumatic drug (DMARD) treatment for 14 early RA patients, using a 1.0-T MRI unit. One-slice DCE-MRI was analysed using Dynamika version 4.2. The number of enhancing voxels (Nvoxel), the initial rate of enhancement (IRE), the maximum enhancement (ME), ME×Nvoxel, and IRE×Nvoxel were calculated for wrist and 2nd–5th metacarpophalangeal (MCP) joints. Conventional MR images were evaluated using the RA MRI scoring system (RAMRIS) synovitis score. Results: Using DCE-MRI, enhancement was demonstrated in 61.5% of healthy persons and in 91.7% of RA patients at baseline, with a median Nvoxel of 3 and 362, respectively. At baseline, all parameters were higher for patients than for healthy persons (all p ≤ 0.003). Only one patient had a baseline RAMRIS synovitis score below the 95th percentile of the healthy persons. The corresponding number of patients was 3 for Nvoxel, ME×Nvoxel and IRE×Nvoxel, and 10 for IRE and ME. The RAMRIS synovitis score and IRE showed the highest responsiveness, with a standardized response mean (SRM) of –1.00 and –0.88, respectively. Conclusions: The RAMRIS synovitis scoring of conventional MRI, and to a lesser extent the one-slice DCE-MRI parameters of synovial volume, differentiated early RA patients and healthy persons. The decrease in RAMRIS synovitis score, Nvoxel, and IRE showed sensitivity to change during treatment.